1995
DOI: 10.1007/bf01976497
|View full text |Cite
|
Sign up to set email alerts
|

Expression of snowdrop lectin in transgenic tobacco plants results in added protection against aphids

Abstract: The range of sap-sucking insect pests to which GNA, (the mannose specific lectin from snowdrops (Galanthus nivalis)) has been shown to be insecticidal in artificial diets has been extended to include the peach potato aphid (Myzuspersicae). A gene construct for constitutive expression of GNA from the CaMV35S gene promoter has been introduced into tobacco plants. A transgenic tobacco line which expresses high levels of GNA has been shown to have enhanced resistance to M. persicae in leaf disc and whole plant bio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
130
0
1

Year Published

1998
1998
2010
2010

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 238 publications
(138 citation statements)
references
References 21 publications
(17 reference statements)
6
130
0
1
Order By: Relevance
“…The snowdrop lectin, GNA, is toxic to brown planthopper (Nilaparvata lugens; Powell et al, 1998;Tang et al, 2001) and tomato moth (Lacanobia oleracea) larvae (Fitches et al, 1997;Gatehouse et al, 1997Gatehouse et al, , 1999 as well as to several aphid species (Hilder et al, 1995;Rahbé et al, 1995;Gatehouse et al, 1996;Sauvion et al, 1996). Concanavalin A (lectin from Canavalia ensiformis) shows significant antimetabolic activity toward third-instar nymphs of taro planthopper (Tarophagous proserpina; Powell, 2001).…”
mentioning
confidence: 99%
“…The snowdrop lectin, GNA, is toxic to brown planthopper (Nilaparvata lugens; Powell et al, 1998;Tang et al, 2001) and tomato moth (Lacanobia oleracea) larvae (Fitches et al, 1997;Gatehouse et al, 1997Gatehouse et al, , 1999 as well as to several aphid species (Hilder et al, 1995;Rahbé et al, 1995;Gatehouse et al, 1996;Sauvion et al, 1996). Concanavalin A (lectin from Canavalia ensiformis) shows significant antimetabolic activity toward third-instar nymphs of taro planthopper (Tarophagous proserpina; Powell, 2001).…”
mentioning
confidence: 99%
“…GNA is one of the most closely studied plant lectins, mainly because it was the first plant lectin shown to be active against Hemiptera and the protein is easy to purify (Shi et al, 1994;Hilder et al, 1995). It specifically binds to high-mannose glycans, in particular to terminal mannose residues.…”
Section: Gna: a Mannose-specific Lectin With Negative Effects On Sevementioning
confidence: 99%
“…Controls containing no protein and containing no diet were set up for each trial. The diet solution was incorporated into feeding vessels based on those described by Hilder et al [4]. Petri dishes (90 mm diameter) were lined with water-soaked filter paper.…”
Section: Artificial Diet Bioassaysmentioning
confidence: 99%
“…Recent studies showed that some plant lectins were toxic to sapsucking insects in artificial diet assays [2,3], among which the lectin (GNA) from snowdrop (Galanthus nivalis), encoded by the gna gene, was the most toxic. Transgenic tobacco and rice expressing GNA showed significant insecticidal activity towards the peach potato aphids (Myzus persicae Sulzer) [4] and rice planthoppers including Nilaparvata lugens [5,6] and Laodelphax striatellus [7] respectively in bioassay and feeding tests.…”
Section: Introductionmentioning
confidence: 99%